Il padre muto e la vocazione alla sterilità. Parte prima: misoginia, femminismo e crisi della paternità - Testoni, Ines (Il sogno della farfalla, 2009)
The article considers the sense of crisis that characterizes the reproductive question in the West, under the symbolic coordinates that link the North and South of Europe. It discusses the change of the traditional generational mandate, that was created by feminism and by thoughts about sexual differences that have promoted a new point of view on maternity. Deciphering the high and low moments of the literary language, it tracks the role of man and his responsibilities in this impasse, supported by the crisis of fatherhood that has also contaminated feminism. The analysis therefore considers misogyny and the vocation to sterility as symptoms of men’s inability (caused by the decline of traditional ethics), to respond to women on a common project of procreation. The fulcrum, on which this research rotates, concerns the loss of sense of the word father, or the silence of the father. Through an analysis of the misogynist literature produced between the 1800s and 1900s pivoting on the concept of a decline of traditional western thinking as offered to us by the philosopher Emanuele Severino, the article analyses the crisis of morals. In particular, it considers the continuity before: maintenance of traditionalism, the Southern question and mafia familism. The study is divided into two parts: the first part outlines the theoretical framework that justifies the interpretation of the theatrical and literary texts that are considered in the second part and that are utilized as social indicators of the cultural milieu between the two centuries. The conclusions show the impossibility of considering the return of traditionalism as a resolution, from which specific cultural and political implications may derive.